Lipase mediated simultaneous esterification and epoxidation of oleic acid for the production of alkylepoxystearates - Orellana Coca Åkerman, Cecilia; Billakanti, Jagan M.; Mattiasson, Bo; Hatti-Kaul, Rajni (Journal of Molecular Catalysis B: Enzymatic, 2007)
Epoxy alkylstearates were synthesized by lipase catalysed esterification and perhydrolysis followed by epoxidation of oleic acid in a one-pot process. Immobilized Candida antarctica lipase (Novozym 435) was used as the catalyst. The esterification reaction occurred relatively quickly and was followed by epoxidation of the alkyl ester and the remaining fatty acid. Higher degree of esterification was achieved with n-octanol, n-hexanol and n-butanol as compared to that with ethanol and iso-propanol. The rate and yield of epoxidation was enhanced with iso-propanol but was lowered with the other alcohols. The lipase suffered significant loss in activity during the reaction primarily due to hydrogen peroxide. The presence of alcohols, in particular ethanol. further contributed to the enzyme inactivation. The epoxidation reaction could be improved by step-wise addition of the lipase. (c) 2006 Elsevier B.V All rights reserved.